Improving Consistency in Performance Measurement System Design The Case of the Colombian Public Schools - Salazar Rua, Robinson (Cham : Springer Nature Switzerland : Imprint: Springer, 2023)
This book analyzes behavioral distortions in public schools and delineates outcome-based performance measurement systems that can prevent and mitigate them. An instrumental view of dynamic performance management (DPM) is used to support the endeavor by identifying how performance drivers affect end results of outcome and output, how end results affect strategic resources, and how strategic resources and benchmarks define the dynamics of performance drivers. This approach is also used to promote a shift from an output-oriented to an outcome-oriented view in performance management, with the aim of achieving sustainable results in the long term. The book also includes a comprehensive literature review at the end of each chapter, intended to strengthen readers' knowledge and encourage further research. Given its scope, the book will appeal to graduate students in public management, researchers in performance management, system dynamics, and education, and decision-makers in public schools.
Chapter 1 Affecting organizational behavior through performance measurement systems -- Chapter 2: Implementing performance measurement systems to hold public schools accountable for -- educational quality -- Chapter 3: Exploring the conceptual roots of outcome-oriented performance measurement systems- Chapter 4: Using Dynamic Performance Management to outline outcome-oriented performance measurement systems in public schools- Chapter 5: Extending the system boundaries to enhance school performance -- Appendices.
Keywords: Management; Education and state; Social sciences -- Data processing; Education; Public administration; Management; Education Policy; Computer Application in Social and Behavioral Sciences; Education; Public Administration